2013
DOI: 10.2174/092986713804870783
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy Changes After Antipsychotic Treatment

Abstract: Proton magnetic resonance spectroscopy ((1)H MRS) enables the observation of brain function in vivo. Several brain metabolites can be measured by the means of (1)H MRS: N-acetylaspartate (NAA), choline containing compounds (Cho), myo-inositol (mI) and glutamate (Glu), glutamine (Gln) and GABA (together as Glx complex or separately). (1)H MRS measures have been found to be abnormal in psychotic disorders such as schizophrenia. Here we specifically review the influence exerted by antipsychotic drugs on brain met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 75 publications
0
14
1
Order By: Relevance
“…The DAergic, GLUergic and GABAergic systems are disrupted in SZ and other disorders with a psychotic component (Egerton and Stone, 2012; Eyles et al, 2012; Howes and Kapur, 2009; Lisman et al, 2008; Szulc et al, 2013). They and the 5HTergic system mutually interact and are direct or indirect targets of the AAPDs used to treat those disorders (Del Arco and Mora, 2005, 2008; Di Pietro and Seamans, 2007; Gao et al, 2003; Howes and Kapur, 2009; Kapur and Remington, 1996; Lisman et al, 2008; Loskutova, 2001; Marek, 2007; Missale et al, 2006; Sun and Wolf, 2009; Wang et al, 2002; West et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DAergic, GLUergic and GABAergic systems are disrupted in SZ and other disorders with a psychotic component (Egerton and Stone, 2012; Eyles et al, 2012; Howes and Kapur, 2009; Lisman et al, 2008; Szulc et al, 2013). They and the 5HTergic system mutually interact and are direct or indirect targets of the AAPDs used to treat those disorders (Del Arco and Mora, 2005, 2008; Di Pietro and Seamans, 2007; Gao et al, 2003; Howes and Kapur, 2009; Kapur and Remington, 1996; Lisman et al, 2008; Loskutova, 2001; Marek, 2007; Missale et al, 2006; Sun and Wolf, 2009; Wang et al, 2002; West et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions can include the formation of heterodimers consisting of receptors for different transmitters (de Bartolomeis et al, 2013; Missale et al, 2010). Indeed, abnormalities of GLUergic transmission can induce a cascade of events that lead to disruption of DAergic and GABAergic signaling and, in humans and animal models, phenotypes of psychosis and cognitive dysfunction (Egerton and Stone, 2012; Howes and Kapur, 2009; Lisman et al, 2008; O'Donnell, 2012; Szulc et al, 2013). Therefore, we hypothesized that in adult rats treated with OLA as adolescents, GLU and GABA levels should be abnormal in brain regions in which we demonstrated long-lasting alteration of DAergic transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies did not show a treatment effect on glutamate levels in the prefrontal cortex [32][33][34][35], although in one studies improvement of negative symptoms was related to increased Glx levels [32] and improvement on total PANSS to lower Glx levels [9]. The observed changes by antipsychotics on Glx levels may be caused by their dopaminergic effects on glutamatergic receptor activity and density and modulation of glutamate release [36].…”
Section: Researchmentioning
confidence: 98%
“…The reported effects may be dependent on treatment states of the subjects [9]. Studies on the effect of antipsychotics have shown both increases and decreases of prefrontal metabolite levels that may be dependent on type, dose or duration of treatment [3,5,9], but reduced Glx and NAA levels have been related to stronger dopamine D2 receptor antagonists [5,6,8].…”
Section: Experimental Procedures Subjectsmentioning
confidence: 99%
“…Therefore, NAA is mainly of neuronal origin and changes in NAA levels are thought to reflect neuronal function, viability or density (See review by (Rae 2014)). While NAA changes have been observed in different regions of schizophrenic patients (See systematic reviews and metaanalyses by (Kraguljac et al 2012;Steen et al 2005)), potential confounds of APD treatment on these observations are still in debate; some studies have reported an increase or correction of NAA levels with APD treatment (Bertolino et al 2001;Fannon et al 2003;Szulc et al 2005;Szulc et al 2013); other studies have observed no significant changes with APDs (Bustillo et al 2008;Bustillo et al 2010). Examination of NAA levels with APD treatment in 'normal' rodents without psychopathological effects can help address this issue.…”
Section: Introductionmentioning
confidence: 99%